Refining an Asynchronous Telerehabilitation Platform for Speech-Language Pathology: Engaging End-Users in the Process - Hill, Annie J.; Breslin, Hugh M. (Frontiers in Human Neuroscience, 2016)
Asynchronous telerehabilitation in which computer-based interventions are remotely monitored and adapted offline is an emerging service delivery model in the rehabilitation of communication disorders. The asynchronous nature of this model may hold a benefit over its synchronous counterpart by eliminating scheduling issues and thus improving efficiency in a healthcare landscape of constrained resource allocation. The design of asynchronous telerehabilitation platforms should therefore ensure efficiency and flexibility. The authors have been engaged in a program of research to develop and evaluate an asynchronous telerehabilitation platform for use in speech-language pathology. eSALT is a novel asynchronous telerehabilitation platform in which clinicians design and individualize therapy tasks for upload to a client’s mobile device. An inbuilt telerehabilitation module allows for remote monitoring and updating of tasks. This paper introduces eSALT and reports outcomes from an usability study that considered the needs of two end-user groups, people with aphasia and clinicians, in the on-going refinement of eSALT. In the study participants with aphasia were paired with clinicians who used eSALT to design and customize therapy tasks. After training on the mobile device the participants engaged in therapy at home for a period of three weeks, while clinicians remotely monitored and updated tasks. Following the home trial, participants and clinicians engaged in semi-structured interviews and completed surveys on the usability of eSALT and their satisfaction with the platform. Content analysis of data involving five participants and three clinicians revealed a number of usability themes including ease of use, user support, satisfaction, limitations and potential improvements. These findings were translated into a number of refinements of the eSALT platform including the development of a client interface for use on the Apple iPad®, greater variety in feedback options to both the participant and clinician, automatic transfer of results to the clinician and expansion of the task template list. This research highlights the importance of including end-users in the process of technology refinement, in order to ensure effective and efficient use of the technology. Future directions for research are discussed including clinical trials in which the effectiveness of and adherence to intervention protocols using asynchronous telerehabilitation are examined.